PENGEMBANGAN PERANGKAT PEMBELAJARAN FISIKA BERBASIS STRATEGI METAKOGNITIF UNTUK MENINGKATKAN HASIL BELAJAR SISWA SMA - Silitonga, Haratua Tiur Maria; Panjaitan, Masti (IKIP PGRI Pontianak, 2019)
The study aims to examine the feasibility of a learning device using a metacognitive strategy for use in physics learning for XI-grade high school students. The development of the device is based on the study of the physics learning competencies referring to the 2013 curriculum based on the study of physical learning competencies that refer to the 2013 curriculum. The learning devices that are organized include learning plans and physics study results tests. The method used is Research and Development (R & D) refers to the step developed by the simplified Borg & Gall. The test instrument of learning results consists of 31 questions of multiple choice and has been validated by evaluation experts, physicists, physics education, expert and practitioners. The validation test was tested in 176 high school students in Pontianak City. Expert analysis using the validity of the content of Aiken's V provides a 0.77 validity index. The reliability test using SPSS 17.0 provides a reliability index of 0.71. Analysis of the device's effectiveness of metacognitive learning plans developed to improve student learning outcomes through learning trials in class XI students. The results showed that there were significant differences in the learning outcomes of students using the Learning Strategy tool that using the learning devices used in the school is obtained Thitung = 2.055 (Î± = 0.044; df = 59). As such, learning devices are developed worthy of use in physics learning in the XI class.